Valuasi Pasar Obat Herbal: Textual Network Analysis dan Social Network Analysis Berbasis Corpus - Darwan (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This article aims to explore how the symbolic assessment of actors in the phytopharmaca herbal market arena in Indonesia uses one of the market assessment criteria, namely the symbolic value of cognitive anchoring. Based on digital research of the phytopharmaceutical market, The primary data obtained was then visualized using Gephi software and analyzed using a mixed method technique in a corpus-based TNA and SNA to map actor positions and network characteristics between actors. The results show that the consumption of phytopharmaca is a social behavior that manifests in meaning. This reflective process becomes the basis for deciding the community choosing phytopharmaca as medicine. In addition, knowledge and decisions to consume phytopharmaca are influenced by practical considerations, both the influence of individual and group reviews, personal experience, and information that forms a specific understanding. Therefore, the conclusion of this research is that network position visualization pattern actors, including companies, government institutions, educational institutions, and communities that develop research on phytopharmaceutical products to compete in the global market. The impact of the increase in the consumption of phytopharmaca herbal medicines in Indonesia during the covid-19 pandemic. Keywords: market valuation, cognitive anchoring, actor position, TNA, SNA, Phytopharmaceuticals